THE PROBLEM OF PREPARING STUDENTS FOR INNOVATIVE PEDAGOGICAL ACTIVITIES - Ramazonov Jahangir Djalolovich; Odilov Muhammadjon Usmonjon o’g’li (Web of Journals Publishing, 2024)
In this article, the training of highly qualified and competitive personnel in the higher education system brings feedback on the most important tasks of this system and the psychological characteristics of the innovative activities of future educators.
Keywords: Innovation, navation, technology, complexity, systematicity, innovative environment, innovative pedagogical activity, optimallig.